Changes of the Public Attitudes of China to Domestic COVID-19 Vaccination After the Vaccines Were Approved: A Semantic Network and Sentiment Analysis Based on Sina Weibo Texts - Gao, Hao; Guo, Difan; Wu, Jing; Zhao, Qingting; Li, Lina (Frontiers in Public Health, 2021)
Introduction: On 31st December 2020, the Chinese government announced that the domestic COVID-19 vaccines have obtained approval for conditional marketing and are free for vaccination. This release drove the public’s attention and intense debates on social media, which reflected public attitudes to the domestic vaccine. This study examines whether the public concerns and public attitudes to domestic COVID-19 vaccines changed after the official announcement. Methods: This article uses big data analytics to research, including semantic network and sentiment analysis. The semantic network is to obtain the public concerns about domestic vaccines. Sentiment analysis reflects the public sentiments to the domestic vaccines and the emotional changes by comparing the specific sentiments shown on the posts before and after the official announcement. Results: There exists a correlation between public concerns about domestic vaccines before and after the official announcement. According to semantic network analysis, public concerns about vaccines have changed after the official announcement. The public focused on performance issues of vaccines before the official approval, but they cared more about practical issues of vaccination after that. Sentiment analysis showed that both positive and negative emotions increased among the public after the official announcement. ‘Good’ as the most increased positive emotion indicated great public appreciation for production capacity and free vaccination. ‘Fear’ as the significantly increased negative emotion reflected the public concern about the safety of the vaccines. Conclusion: The official announcement of the approval for marketing improved the Chinese public acceptance of the domestic COVID-19 vaccines. In addition, safety and effectiveness are vital factors influencing public vaccine hesitancy.